RNAi: key technological aspects - Samarsky, Dmitry; Faherty, Ciaran (Henry Stewart Talks, 2007)
General outline of RNAi technology, Basic principles and mechanisms of RNAi, RNAi technological aspects, delivery, activity and specificity of RNAi compounds, Key factors defining RNAi application, Test system, Target throughput, Phenotypic readout
Reviewed at 2015/10/14